(untitled) (Al-Academy, 2016)
Problem of research as defined, including the following:what is impact organizing of configuration for still life in paintings of students in the Department of Art Education in subject of colors ?Study of well training for organized in painting of still life is necessary for a teacher of art education to contribute effectively to the performance of his letter, so is this research in response to the public goals for a subject of art education. The current research aims to:1. Impact organization of configuration for still life in paintings of students in the Department of Art Education for the first grade in subject of colors2. Role organization of configuration for still life in the painting to serve the educational process in subject of colors.Students of first grade /Department of Art Education were identified, who are studying in the College of Fine Arts as society for Research and his appointed (74) students were selected (64) students.In the current search follow the curriculum (experimental - analytical) has been used analysis form for paintings of research community, consists of 40 paragraph and the authenticity of the tool was verified during their presentation to the group of experts. Still life has been determined which have been analyzed by experts in the art.In order to reach for the results of the research, the researcher used the following statistical means:1- Pearson’s correlation coefficient (PERSON): The patch degree stability to extract according to the observation in a manner tool to assess performance skill.2-T- test: Used for comparison between the two groups (Z , V) .After data unloading in paintings for the research community the results to found: - There are simple significant differences between the ranks for the experimental group.- To verify the validity of the results, The researcher used law of T-test on analysis the expert for paintings the students of the two groups (Z,V).The researcher used the correlation coefficient to know the parity between the two groups (Z,V) in the collection of skills.The recommendations were: Teaching subject of still life by using the educational program is subject of current research, in order to prove its effectiveness and its feasibility and usefulness.Proposals: Conduct a study to design an educational program according to impact of organization the configuration in other paintings